Menelusuri Para Raja Madura Dari Masa Pra-Islam Hingga Masa Kolonial - Wawan Hernawan (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
The Madurese kings, of Western and Eastern part of Madura, have shown their exsistence in the history of archipelagic kings. However, their exsistence are less influenced and less famous compared to the kings of Java, Sunda or Bali origin. The investigation of Madurese kings (of Western and Eastern part of Madura) aims at finding the authenticity of their existences. This study is important to counter global figures idolisations and to shows the local people about their local ideals who have given significant contribution to the foundation of Indonesian history. This study employs historical research method to dig information on the reign of the kingdom. This study shows that: first, one source informed (the validity is unknown) concerning the genealogy of the story related to princes Bendoro Gung and Raden Segoro showed the trace of people coming to Madura from the West side through to the East. Second, in pre-Islamic period, based on several inscription and manuscript (kakawin, serat, kidung, dan babad), showed that there are more information given to the role of Eastern Madurese than that of Western. The role of Western Madurese only available in Islamic period by providing the story of Prince Pratanu’s journey to Mataram and back to West Madura (Bangkalan), then followed by several kings of Western Madura. Meanwhile, Eastern Madura kingdom (Sumenep) have been governed at least by 35 kings since Arya Wiraraja to Bendoro Abdurrahman. The journey of Madurese kings continued until the arrival of Vereenigde OostIndische Compagnie (VOC) and Dutch collonialism.